Dilemas bioéticos en la práctica asistencial de la Anatomía Patológica - Verny Danilo Cedeño Alvarado; Gustavo Javier Palma Mieles; Eugenio Radamés Borroto Cruz (Revista San Gregorio, 2026)
Pathological Anatomy plays a fundamental role in the diagnosis, prognosis, and therapeutic guidance of various diseases. Although the pathologist’s contact with the patient is usually indirect, healthcare practice in this specialty involves the handling of biological samples, clinical data, genetic information, and sensitive diagnostic results, which gives rise to important bioethical dilemmas. The objective of this study was to analyze the main bioethical dilemmas present in the healthcare practice of Pathological Anatomy. A position article with a reflective-critical approach was developed, supported by a documentary review of scientific literature, regulatory documents, and reference texts on bioethics. The analysis identified informed consent, confidentiality of clinical information, protection of personal data, disclosure of results to third parties, secondary use of biological specimens, management of genetic information, and equity in access to highly complex diagnostic technologies as the main dilemmas. It is concluded that pathological anatomy practice has an essential ethical dimension that requires institutional protocols, rigorous protection of information, equitable access to specialized services, and ongoing bioethical training. These elements strengthen safer, more responsible care centered on patients’ rights.